Exploration of Patellidae from Coastal Waters of Ambon Island, Indonesia - Pattipeilohy, Dwien E.; Liline, Sintje; Salmanu, Sriyanti A.I; Tri Santi Kurnia (Universitas PGRI Palembang, 2023)
Patellidae are gastropods that live in intertidal zones and sublittoral zones of shallow rocky shores because Patellidae are usually attached to boulders. Patellidae belongs to the order Archaeogastropoda and generally only has two genera, namely Cellana and Patella. Patellidae are also found in the waters of Ambon Island, namely in the Hukurila Village and Allang Village. This study aims to determine the type, morphometrics, density, and proximate levels of Patellidae in the waters of Ambon Island. Samples were taken using purposive sampling with cruising methods. The Patellidae are attached to the substrate. Samples from two locations were taken and put into plastic, and then the type and morphometrics were identified at the Basic Biology Laboratory of the Faculty of Teacher Training and Education, Pattimura University. Proximate levels were conducted at the Basic Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Pattimura University. This research was conducted from October 15, 2022, to November 15, 2022. Based on the results, two species of the Patellidae family were found in Ambon Island, namely C. testudinaria and P. flexuosa. The results of the calculation of morphometric Patellidae in the Waters of Ambon Island showed that the species C. testudinaria in the Waters of Hukurila Village has a larger morphometric characteristic size compared to the species C. testudinaria and P. flexuosa in the Waters of Allang Village. More individuals of P. flexuosa species were found in Alang village than C. testudinaria species, while many C. testudinaria species were found in Hukurila village. Based on the proximate analysis results, Patellidae from the waters of Ambon Island have nutritious and good nutritional content to be used as food ingredients.